VarR controls colonization and virulence in the marine macroalgal pathogen Nautella italica R11 - Gardiner, Melissa; Fernandes, Neil D.; Nowakowski, Dennis; Raftery, Mark; Kjelleberg, Staffan; Zhong, Ling; Thomas, Torsten; Egan, Suhelen (Frontiers in Microbiology, 2015)
There is increasing evidence to suggest that macroalgae (seaweeds) are susceptible to infectious disease. However, to date, little is known about the mechanisms that facilitate the colonization and virulence of microbial seaweed pathogens. One well-described example of a seaweed disease is the bleaching of the red alga Delisea pulchra, which can be caused by the bacterium Nautella italica R11, a member of the Roseobacter clade. This pathogen contains a unique luxR-type gene, varR, which we hypothesize controls its colonization and virulence. We show here that a varR knock-out strain is deficient in its ability to cause disease in D. pulchra and is defective in biofilm formation and attachment to a common algal polysaccharide. Moreover complementation of the varR gene in trans can restore these functions to the wild type levels. Proteomic analysis of bacterial cells in planktonic and biofilm growth highlight the potential importance of nitrogen scavenging, mobilization of energy reserves, and stress resistance in the biofilm lifestyle of N. italica R11. Moreover, we show that VarR regulates the expression of a specific subset of biofilm-associated proteins. Taken together these data suggest that VarR controls colonization and persistence of N. italica R11 on the surface of a macroalgal host and that it is an important regulator of virulence.